THE EXPLANATION OF THE CHILD AND WIFE'S INHERITANCE RIGHTS AS A RESULT OF SIRI LEGITIMATE MARRIAGE - Dwi Tatak Subagiyo; Desi Nurkristia Tedjawati (Universitas Lampung, 2022)
Children out of wedlock (illegitimate children), according to Law No.1/1974, still have a legal relationship with their mother and their mother's family. In contrast, in KUHPdt/BW, the legal relationship exists only with the person who acknowledges it. The Constitutional Court stated that Article 43 paragraph (1) of the Marriage Law is conditional unconstitutional. The decision of Constitutional Court Number: 46 / PUU-VIII / 2010 regarding the status of children born outside of marriage raises new problems regarding the distribution of inheritance from the father to the child. In Islamic law, the distribution of inheritance cannot be implemented because, according to the concept of Islamic inheritance law, there are conditions such as lineage or a legal relationship according to marriage. In that regard, this study will comprehensively discuss the characteristics of inheritance distribution to children out of wedlock in positive Indonesian law, as well as the castration of a wife's inheritance rights as a result of the legal consequences of inheritance distribution to children out of wedlock based on Constitutional Court Decision Number: 46/PUU-VIII/2010. The method used in this research is normative legal research using the case approach method by analyzing the relevant laws and regulations and examining cases related to inheritance rights for children born out of wedlock. The results confirmed the apparent support for the inheritance rights of illegitimate children is indeed in the mother's family line. Article 863 BW states that if the inheritance leaves a legal offspring or husband or wife, the illegitimate children inherit 1/3 of what legitimate children would receive.